Implementation of the Protocol objectives on the issues of water and health according to international obligations of the Republic of Belarus - Dubianok, Sniazhana; Holad, Yuliya (Journal of the Belarusian State University. Ecology, 2024)
Since 2003, the Republic of Belarus has been a party to the 1992 Convention on the Protection and Use of Transboundary Watercourses and International Lakes, and since 2009 the country has acceded to the Protocol on Water and Health, adopted in 1999 to the said Convention. The main objective of the Protocol on Water and Health is to protect human health and well-being by improving water management, including the protection of aquatic ecosystems and the reduction of water-related diseases. The Protocol on Water and Health includes 20 target areas for which countries set national targets to be achieved or maintained. The Protocol on Water and Health is directly focused on protecting human health and well-being within the framework of sustainable development, and is therefore linked to the Sustainable Development Goals (SDGs) adopted by the UN in 2015, namely SDG 3 and SDG 6. In 2021, in order to implement the Protocol on Water and Health, the Republic of Belarus approved the Set of Measures to meet the obligations undertaken by the Republic of Belarus under the Protocol on Water and Health to the 1992 Convention on the Protection and Use of Transboundary Watercourses and International Lakes until 2030.The article assesses the current progress in the implementation of the four objectives of the Set of Measures addressing issues of wastewater discharge into the environment, in synergy with the implementation of SDG 6 objectives.SDG 6 targets cover two target areas of the Protocol on Water and Health: Protocol Area X – “Frequency of discharges of untreated storm water flows from wastewater sewer systems” (1 task and 2 targets) and Protocol Area XI – “Quality of wastewater discharges from wastewater treatment plants” (3 tasks and 3 targets).
Keywords: water resources; water use; wastewater; state water cadaster; sustainable development goals